KOMITMEN GURU DALAM MELAKSANAKAN TUGAS DI SMK SWASTA KELOMPOK BISNIS MANAJEMEN KECAMATAN PADANG BARAT KOTA PADANG - Zulhasri (Universitas Negeri Padang, 2014)
The goal of this research are to see information about the Teachers Commitment To Carry Out The Task. The population is 101 teachers and the sample is 51 people that taken by stratified random sampling. The instrument of this research is question with Likert scale models that had tested for validity and realibility. Data analyzed using mean score and performance level. The result of this research are the Teachers Commitment To Carry Out The Task In Smk Swasta Kelompok Bisnis Manajemen Kecamatan Padang Barat Kota Padang stay in good enough category. Key word : Teachers Commitment